Control of rural house infestation by Triatoma infestans in the Bolivian Chaco using a microencapsulated insecticide formulation - Gorla, David Eladio (2015)
Background: Triatoma infestans, the main vector of Trypanosoma cruzi (causative agent of Chagas disease) has been successfully eliminated over much of its original geographic distribution over the southern cone countries of South America. However, populations of the species are still infesting houses of rural communities of the Gran Chaco region of Argentina and Bolivia. This study reports for the first time a large-scale effect of a vector control intervention using a microencapsulated formulation of organophosphates and insect growth regulator on house infestation by T. infestans, in the southwestern region of Santa Cruz de la Sierra Department, within the Bolivian chaco. Methods: The vector control intervention included the treatment and entomological evaluation of 1626 individually coded and georeferenced houses with the microencapsulated formulation. House infestation by T. infestans was evaluated by active searches with fixed capture effort carried out before and after two, 16 and 32 months of the treatment application. Results: House infestation prevalence was 30.5% before the intervention, spatially aggregated in two clusters of 38 and 25 localities that showed 41% and 38% house infestation by T. infestans. Infestation prevalence was reduced to 2.4% two months after the intervention and remained very low (1.7%) until the end of the study after 32 months of the control intervention, without any other additional vector control intervention. Conclusions: The obtained results show an important long lasting effect on house protection against triatomine infestation in a region of known pyrethroid resistant populations of T. infestans, as the result of the slow release of the active ingredients, protected by the formulation microcapsule.